2019
DOI: 10.1186/s12884-019-2536-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions about caesarean section deliveries and their role in reducing perinatal and neonatal mortality in the Upper West Region of Ghana; a cross-sectional study

Abstract: Background Maternal perceptions about caesarean section contribute to delayed presentation of women for emergency obstetric care. This increases the risks of perinatal and neonatal mortality and slows down the reductions needed to achieve the sustainable development goal (SDG) target of reducing neonatal mortality and ending new-born deaths. The aim of the study is to determine maternal perceptions about caesarean section deliveries and their role in reducing neonatal mortality at a regional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
9
1
4
Order By: Relevance
“…[1] A further reason may be the aversion towards CS [6] and the generally poor knowledge of reproductive health issues. [7] This seems corroborated by Prah and colleagues who found that only 45% of their respondents who were pregnant women attending antenatal clinic could correctly identify one indication for CS. [8] The findings of these studies are limited by the fact that they involved mixed populations of women many of whom had never experienced a Caesarean delivery.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…[1] A further reason may be the aversion towards CS [6] and the generally poor knowledge of reproductive health issues. [7] This seems corroborated by Prah and colleagues who found that only 45% of their respondents who were pregnant women attending antenatal clinic could correctly identify one indication for CS. [8] The findings of these studies are limited by the fact that they involved mixed populations of women many of whom had never experienced a Caesarean delivery.…”
Section: Introductionmentioning
confidence: 76%
“…counselling, poor maternal recall due to many competing demands immediately after delivery, the general lack of information on reproductive health matters and the lack of importance attached to the issue. [1,10,12] Though it has been shown in some reports from LMICs that women generally have poor knowledge of reproductive health issues, [7,8] their recall of information made available to them also depends on the importance they attach to that information. Certain basic information such as mode of delivery had almost 100% recall in previous studies.…”
Section: Annals Of Health Research Volume 6 Issue No 4 2020_______mentioning
confidence: 99%
“…The research found that uneducated women associate natural birth with true motherhood and C-section with incapability of a mother or luxury. A study in Ghana concluded that women who are deprived of formal education and are unemployed show a poor perception of the Caesarian section and women see the Caesarian section as a reproductive failure whereas, vaginal delivery is a symbol of womanhood (Gandau, et al, 2019). Whereas, qualified/educated women tend to focus more on their health and are sensitive to baby's birth defects which may result in normal delivery therefore, educated women consider C-section as a safer option.…”
Section: Findings Perception About Caesarian Section Concerning Qualificationmentioning
confidence: 99%
“…‗The greatest increase was seen in women with a higher educational level and those in the richest wealth quintile' (Mumtaz, Bahk, & Khang, 2017). A study in Ghana also revealed that economically poorer women perceived C-section as a long term disease as the recovery time is longer after C-section and it keeps women from doing their domestic chores and economic affairs therefore they avoid C-section and widespread of such perceptions runs in the community (Gandau, et al, 2019).…”
Section: The Variance Of Perception and Experience With Socioeconomic Startmentioning
confidence: 99%
“…Altogether, 5 scientific papers involving 1 resident, 4 house officers and 1 medical officer have been published. [15][16][17][18][19] There are 2 other manuscripts, one by a resident and another with a house officer waiting for posting, near publication, among others at different stages of development. Five papers have also been presented at meetings, national and international conferences including two by the residents and one by a house officer.…”
Section: Research Internships For Doctorsmentioning
confidence: 99%